The Protracted Magmatism and Hydrothermal Activity Associated with the Gibraltar Porphyry Cu-Mo Deposit, South Central British Columbia, Canada. - Kobylinski, Christopher (Université d'Ottawa / University of Ottawa, 2019)
The Gibraltar porphyry-Cu deposit is a large open pit porphyry Cu mine in Canada with the geological tonnage (production and reserves) of 3.2 Mt Cu. The Gibraltar deposit is hosted by the Granite Mountain Batholith (GMB), a tonalitic batholith with the surface exposure over 150 km2. All rocks within the batholith are tonalites with minor quartz diorites. The batholith intrudes into mafic volcanoclastic rocks of the Nicola group in the Quesnel terrane of the Canadian Cordillera. The Cu mineralization at Gibraltar is confined to a small 4.5 km2 area in the central part of the batholith and occurs primarily as disseminated chalcopyrite. New U-Pb dating on zircon shows protracted late Triassic magmatism spanning ~25 m.y. for the formation of the GMB. Early magmatism is dated at 229.2±4.4 Ma in unmineralized tonalites. Later, at least three magmatism form the Cu mineralization during a period spanning from 218.9±3.1 Ma to 205.8±2.1 Ma. These fertile magmas form in a more mature arc setting, superseded early barren magmatic activity in a more juvenile arc setting for the bulk of the GMB. Epidote in the GMB shows compositional zoning with Fe-poor cores and Fe-rich rims. The zoning in the mineralized intrusions likely reflects changes in hydrothermal fluid, from S-rich to S-poor. The data from the Gibraltar deposit shows that an economic porphyry Cu deposit may be found in igneous rocks with low Sr/Y in bulk rocks and low Eu/Eu* in zircon. In the Gibraltar deposit, Ce anomalies in zircon reflect oxidation conditions and are correlated with Cu resource associated with their respective intrusion.
Keywords: Zircon; Epidote; Porphyry; Copper; Alteration; U-Pb; Ce anomaly; Eu anomaly; Zoning; Sr/Y; Trace elements in Zircon; Ce4+/Ce3+